Anaerobic Ammonium Oxidation in Acidic Red Soils - Wu, Jiapeng; Hong, Yiguo; He, Xiang; Jiao, Lijing; Wen, Xiaomei; Chen, Shuai; Chen, Guangshi; Li, Yiben; Huang, Tianzheng; Hu, Yaohao; Liu, Xiaohan (Frontiers in Microbiology, 2018)
Anaerobic ammonium oxidation (anammox) has been proven to be an important nitrogen removal process in terrestrial ecosystems, particularly paddy soils. However, the contribution of anammox in acidic red soils to nitrogen loss has not been well documented to date. Here, we investigated the activity, abundance, and distribution of anammox bacteria in red soils collected in 9 provinces of Southern China. High-throughput sequencing analysis showed that Candidatus Brocadia dominates the anammox bacterial community (93.03% of sequence reads). Quantification of the hydrazine synthase gene (hzsB) and anammox 16S rRNA gene indicated that the abundance of anammox bacteria ranged from 6.20 × 106 to 1.81 × 109 and 4.81 × 106 to 4.54 × 108 copies per gram of dry weight, respectively. Contributions to nitrogen removal by anammox were measured by a 15N isotope-pairing assay. Anammox rates in red soil ranged from 0.01 to 0.59 nmol N g-1 h-1, contributing 16.67-53.27% to N2 production in the studied area, and the total amount of removed nitrogen by anammox was estimated at 2.33 Tg N per year in the natural red soils of southern China. Pearson correlation analyses revealed that the distribution of anammox bacteria significantly correlated with the concentration of nitrate and pH, whereas the abundance and activity of anammox bacteria were significantly influenced by the nitrate and total nitrogen concentrations. Our findings demonstrate that Candidatus Brocadia dominates anammox bacterial communities in acidic red soils and plays an important role in nitrogen loss of the red soil in Southern China.